the Pemanfaatan Google Classroom Dalam Pembelajaran Komunikasi Guru Dan Siswa : Pemanfaatan Google Classroom Guru Dan Siswa - muhamma-raden-dewa-lanang, dewa-lanang (Lentera Jurnal Pengabdian Masyarakat, 2023)
The Covid-19 virus outbreak in Indonesia has caused various activities to be carried out from home. The learning process at school is no exception, where teachers must be able to create learning media that can be operated effectively by students from home. The problem of this research is the use of the Google Classroom application in the learning process at SD N 136 Palembang. The aim to be achieved is to find out and analyze the use of the Google Classroom application in the learning process at SD N 136 Palembang. The author uses a qualitative research method with a descriptive method, by collecting data through interviews, documentation and observation. The research subjects included the school principal, class IV, V and VI teachers, and 4 students were taken from each class IV, V and VI. The research results show that the Google Classroom application is a learning medium that is very flexible in place and time, and is also effective in delivering material and collecting assignments because it is paperless. Each teacher can easily upload power point materials, videos and questions. The Google Classroom application makes learning easier because the material presented is like face-to-face classroom learning.